PRÁCTICAS DE SANIDAD EN LOS PROCESOS PRE Y POST ORDEÑO DE HATOS GANADEROS EN EL RECINTO SANTA ROSA DEL CANTÓN PICHINCHA. - López Sabando, Juan Alberto (2023)
Dairy farming is a very important activity throughout the world, both economically and nutritionally, however, the health, welfare and biosecurity of animals in livestock are crucial aspects since they directly affect production, so Maintaining hygienic facilities and taking some preventive measures such as vaccinations is essential since it prevents diseases in animals and in those in charge of animals, avoiding economic losses to producers, which is why this research project had the objectives of diagnosing practices of health in the pre and post milking processes of cattle herds, describe the general aspects of the producers, determine the activities that are carried out, analyze the sanitary aspects and determine compliance with the parameters of good practices in milking in the Santa Rosa enclosure of the Pichincha canton.